2015
DOI: 10.1039/c5ra14548a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and photoelectrochemical properties of TiO2/CuInS2/Bi2S3 core/shell/shell nanorods electrodes

Abstract: The FESEM images (a and b), photocurrent density versus potential (c–v) curves (c) and schematic of the energy level arrangement (d).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Figure b shows the photoconversion efficiency (η) for the Ti_Bi_0, Ti_Bi_15, and Ti_Bi_30 samples. It can be observed that the η values for all the sensitized samples are higher than the pristine TiO 2 NTs (η = 0.11%) . The Ti_Bi_0 sample presented η = 0.27%, and after the heat treatment, the photoconversion efficiency of the Ti_Bi_15 sample (η = 0.44%) increased 4 times.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Figure b shows the photoconversion efficiency (η) for the Ti_Bi_0, Ti_Bi_15, and Ti_Bi_30 samples. It can be observed that the η values for all the sensitized samples are higher than the pristine TiO 2 NTs (η = 0.11%) . The Ti_Bi_0 sample presented η = 0.27%, and after the heat treatment, the photoconversion efficiency of the Ti_Bi_15 sample (η = 0.44%) increased 4 times.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, all sensitized samples reached the photocurrent saturation at a more negative potential. The increase of the PEC’s overall efficiency probably occurs due to the reduction of the external applied bias. , The Ti_Bi_15 photoanode obtained a higher saturated photocurrent (0.3 mA·cm –2 ) than that of other samples. It confirms that the Bi 2 S 3 nanoparticles coating of the TiO 2 NTs surface by the in situ electrochemical method is a simple but effective way to enhance the PEC performance of TiO 2 photoanodes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…(a) and (b). The photoconversion efficiency η of the light energy to chemical energy in the presence of an external applied potential E app can be calculated from the equation as follows : centerηtrue(%true)=[true(total power outputelectrical power inputtrue)/light power input]×100center=jnormalp[Erevnormalotrue|Enormalanormalpnormalptrue|]×100/(I0), where j p is photocurrent density (mA cm −2 ), jnormalpErevnormalo is total power output, jnormalptrue|Enormalanormalpnormalptrue| is electrical power input, and I 0 is the power density of incident light (mW cm −2 ). Erevnormalo is the standard state‐reversible potential (which is 1.23 V (vs. NHE)), and the applied potential is Eapp=EmeasEaoc, where E meas is the electrode potential (vs. SCE) of the working electrode at which photocurrent was measured under illumination and E aoc is the electrode potential (vs. SCE) of the same working electrode under open circuit conditions, in the same electrolyte and under the same illumination.…”
Section: Resultsmentioning
confidence: 99%
“…A series of modification strategies have been carried out to overcome these disadvantages, such as anatase TiO2 NTAs doped with metal, non-metal or semiconductor. Narrow bandgap semiconductors in particular bismuth-based semiconductors have been used to make TiO2 NTAs susceptible to visible, maintain excellent charge transfer and photofluorescence properties [20] . So Bi2S3 have attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%